Bioethanol production from waste paper through fungal biotechnology - Voigt, Paul George (Rhodes University, Faculty of Pharmacy, Pharmacy, 2010)
Bioethanol is likely to be a large contributor to the fuel sector of industry in the near future. Current research trends are geared towards utilizing food crops as substrate for bioethanol fermentation; however, this is the source of much controversy. Utilizing food crops for fuel purposes is anticipated to cause massive food shortages worldwide. Cellulose is the most abundant renewable resource on earth and is subject to a wide array of scientific study in order to utilize the glucose contained within it. Waste paper has a high degree of cellulose associated with it, which makes it an ideal target for cellulose biotechnology with the ultimate end goal of bioethanol production. This study focussed on producing the necessary enzymes to hydrolyse the cellulose found in waste paper and using the sugars produced to produce ethanol. The effects of various printing inks had on the production of sugars and the total envirorunental impact of the effluents produced during the production line were also examined. It was found that the fungus Trichoderma longibrachiatum DSM 769 grown in Mandel's medium with waste newspaper as the sole carbon source at 28 Â°C for 6 days produced extracellular cellulase enzymes with an activity of 0.203 Â± 0.009 FPU.mlâ »Â¹, significantly higher activity as compared to other paper sources. This extracellular cellulase was used to hydrolyse waste newspaper and office paper, with office paper yielding the highest degree of sugar production with an end concentration of 5.80 Â± 0.19 g/1 at 40 Â°C. Analysis by HPLC showed that although glucose was the major product at 4.35 Â± 0.12 g/1, cellobiose was also produced in appreciable amounts (1.97 Â± 0.71 g/1). The sugar solution was used as a substrate for Saccharomyces cerevisiae DSM 1333 and ethanol was produced at a level of 1.79 Â± 0.26 g/1, the presence of which was confirmed by a 600 MHz NMR spectrum. It was found that cellobiose was not fermented by this strain of S. cerevisiae. Certain components of inks (the PAHs phenanthrene and naphthalene) were found to have a slight inhibitory effect (approximately 15% decrease) on the cellulase enzymes at very high concentrations (approximately 600 Î¼g/1 in aqueous medium), while anthracene had no effect. Whole newsprint ink was shown not to sorb glucose. The environmental analysis of the effluents produced showed that in order for the effluents to be discharged into an aqueous ecosystem they would have to be diluted up to 200 times. They were also shown to have the potential to cause severe machinery damage if reused without proper treatment.
Keywords: Biomass energy; Cellulose -- Biodegradation; Waste paper -- Recycling; Biomass chemicals -- Economic aspects; Renewable energy sources; Fungi -- Biotechnology; Enzymes -- Biotechnology